Late quaternary climate variations in West Antarctica and their impact on the marine siliceous microalgae - Olshtynska, A.P.; Ogienko, O.S. (Український антарктичний журнал, 2017)
Main objective is the reconstruction of late Quaternary climatic events in the northern and north-western parts of the Antarctic Peninsula shelf based on species variation, abundance and ecological structure of diatom complex in bottom sediments.